Corporate governance practices and firm performance: evidence from top 20 syaria compliant public listed companies in Malaysia / Muhamad Shamil Aiman Muhtar - Muhtar, Muhamad Shamil Aiman (2018)
Corporate governance practice have been concern issue after Asian Financial Crisis in 1997, many Asian countries start give more attention about corporate governance practice after Asian Financial Crisis occur. Asian Financial Crisis in 1997 including Malaysia, Malaysia has been implemented Malaysia Code of Corporate Governance (NfCCG) as part of Bursa Malaysia (BNIB) listing rules. This study generally to determine main factor of corporate governance that affect firm performance among Top 20 Sharia Compliant Companies and also to identify the relationship between the corporate governance practices and firm performance among Top 20 Sharia Compliant Companies. Thus, this study examines the relationship between corporate governance (board size and board independent) practice and firm performance (return on asset and return on equity). This study obtained data from 20 random sharia public listed company in Malaysia from 2013 to 2017. The result of this study finds that board independent and board size have no significant relationship with firm performance. While the other independent variable which is board size has significant relationship with the firm performance. Based on this study, provide useful information for regulators or policy makers to improve corporate governance policy in fixture, besides that, help to understanding on the relationship between corporate governance and firm performance in Malaysia and improve the economic Malaysia.